1988
DOI: 10.1172/jci113333
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal modulation of the circadian time structure of circulating T and natural killer lymphocyte subsets from healthy subjects.

Abstract: A seasonal modulation of the circadian time structure of circulating T and natural killer (NK> lymphocyte subtypes was documented in five healthy men aged 24-36 yr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(50 citation statements)
references
References 36 publications
(32 reference statements)
4
45
1
Order By: Relevance
“…First, circadian rhythms are known to exist for lymphocyte subsets, including numbers of NK cells (30). If samples were collected from patients at one time of day and from controls at another time of day, as could happen, such a systematic difference could explain results suggesting significant differences between groups.…”
Section: Discussionmentioning
confidence: 99%
“…First, circadian rhythms are known to exist for lymphocyte subsets, including numbers of NK cells (30). If samples were collected from patients at one time of day and from controls at another time of day, as could happen, such a systematic difference could explain results suggesting significant differences between groups.…”
Section: Discussionmentioning
confidence: 99%
“…MGL represented an exclusive marker of myeloid iDCs and it has been demonstrated in vitro that its expression was increased by dexamethasone (Dex) treatment [7]. Up to now little is known on the factors that can modulate the circa-annual rhythm of the human lectins [6,8] on DCs, but extensively studies on the impact of glucocorticoids (GCs) like Dex on DCs were conducted. Rea D. et al showed that Dex affected the viability of DCs, selectively down-regulated the expression of costimulatory molecules reducing their immunostimulatory properties [9].…”
Section: Discussionmentioning
confidence: 99%
“…Levi et al reported that numbers of NK cells from January to June were significantly less than those in August to November 51) , but it is unknown how seasonal variations influence NK cell activities.…”
Section: Discussionmentioning
confidence: 99%
“…We had both NK cell activity and lymphocyte subpopulations measured by an independent laboratory, SRL Inc. (Tokyo, Japan). The NK cell activity was determined using the 51 Cr (Chromium-51) release method 26) at an effector:target (E/T) ratio of 20:1. The 51 Cr release method was performed as follows.…”
Section: Blood Sampling and Immune Variablesmentioning
confidence: 99%
See 1 more Smart Citation